Stars and Misfits: Self-Employment and Labor Market Frictions - Åstebro, Thomas; Chen, Jing; Thompson, Peter (Management Science, 2011)
Recent evidence has shown that entrants into self-employment are disproportionately drawn from the tails of the earnings and ability distributions. This observation is explained by a multitask model of occupational choice in which frictions in the labor market induce mismatches between firms and workers, and misassignment of workers to tasks. The model also yields distinctive predictions relating prior work histories to earnings and to the probability of entry into self-employment. These predictions are tested with the Korean Labor and Income Panel Study, from which we find considerable support for the model. This paper was accepted by Lee Fleming, entrepreneurship and innovation.